KUALITAS LAYANAN DAN KEPUASAN KONSUMEN: PERSEPSI MASYARAKAT SURABAYA TERHADAP RESTORAN JEPANG DI KOTA SURABAYA - Endo W. Kartika (Institute of Research and Community Outreach - Petra Christian University, 2015)
The aim of the research is to identify the construct indicators for service quality based on the Japanese restaurants customer’s perspective in Surabaya, and explain the impact on service quality towards consumer satisfaction. A total of 100 people residing in Surabaya as respondents took part on the research using the DineSERV measurement by Stevens, Knutson, & Patton (1995). The analysis which are conducted consist of the Confirmatory Factor Analysis using SmartPLS 2.0 software, and Multiple Linear Regression using SPPS 23. The findings indicate that DineSERV can be applied as the construct indicators for service quality based on the people of Surabaya. Further result indicates that tangible and assurance dimension were positively but not significantly affect customer satisfaction; reliability and empathy were positively and significantly affect customer satisfaction; and responsiveness was negatively but not significantly affect customer satisfaction.